LEARNING MANAGEMENT SYSTEM AS COVID 19 RISK MITIGATION - Ali Wafa; Muhammad Muhammad; Shofia Shofia (MANAGERE : Indonesian Journal of Educational Management, 2021)
This study aims to analyze the learning management system as a risk mitigation for Covid 19 at an early childhood education institution in Probolinggo Regency. The research method used is a qualitative case study type. In order to get an overview of the Learning Management System Learning as Covid Risk Mitigation in early childhood, the researchers mingled directly in the implementation of learning and made observations and documented learning activities at the institution. Interviews were conducted with principals and teachers. The results of the study indicate that teacher innovation using a learning management system is carried out through; parental involvement, use of online media, selection of materials, assessment, and follow-up. This study implies that teachers must have innovation and creativity in managing their learning according to the targets they have set to generate total motivation and intelligence of students.